2019
DOI: 10.1089/ars.2018.7523
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia and Reactive Oxygen Species as Modulators of Endoplasmic Reticulum and Golgi Homeostasis

Abstract: The identification of these pathways and the key players involved in intercompartmental communication needs suitable animal models, genome-wide association, as well as proteomic studies in humans. The results of those studies will be beneficial for the understanding of the etiology of diseases such as type 2 diabetes, Alzheimer's disease, and cancer, which are associated with ROS, protein aggregation, and glycosylation defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 226 publications
1
17
0
Order By: Relevance
“…However, after 24 h, ROS production decreased in the infected cells, and this pattern was maintained at 48 and 72 hpi ( Figure 7A). These data could be explained by the downregulation of ero1 in the late stages of infection, as the product of this gene is the largest producer of H 2 O 2 in the ER [30]. When we analysed the modulation of ROS production in vivo at 1 and 5 dpi, we found that ROS production in head kidney cells decreased with the time of infection, showing significant inhibition at 5 dpi compared to the uninfected fish ( Figure 7B).…”
Section: Ros Production Modulation During Nodavirus Infectionmentioning
confidence: 87%
“…However, after 24 h, ROS production decreased in the infected cells, and this pattern was maintained at 48 and 72 hpi ( Figure 7A). These data could be explained by the downregulation of ero1 in the late stages of infection, as the product of this gene is the largest producer of H 2 O 2 in the ER [30]. When we analysed the modulation of ROS production in vivo at 1 and 5 dpi, we found that ROS production in head kidney cells decreased with the time of infection, showing significant inhibition at 5 dpi compared to the uninfected fish ( Figure 7B).…”
Section: Ros Production Modulation During Nodavirus Infectionmentioning
confidence: 87%
“…Emerging evidence suggests that the Golgi apparatus (GA) can directly or indirectly affect intracellular Ca 2+ fluxes, ROS, metabolism, intra-organelle pH, protein and membrane trafficking and thereby contribute to cell migration/invasion [[21], [22], [23], [24], [25]]. Although these roles have been ascribed to the GA, the intricate molecular mechanisms involved in the control of such processes are still mostly unidentified.…”
Section: Introductionmentioning
confidence: 99%
“…However, RyR2 is the most valuable player [7–9]. The hypoxic increase in [Ca 2+ ] i in PASMCs has been thought to be attributed to the enhanced production of intracellular reactive oxygen species (ROS) due to their specific effects on ion channels [10–13]. Mitochondria-derived ROS levels are regulated by intracellular Ca 2+ levels.…”
Section: Introductionmentioning
confidence: 99%